Poetries of Abandonment: A Study of Plath and Glück - Abdelmoneim, Yara (AUC Knowledge Fountain, 2025)
This thesis explores the intersection between literature and trauma, which can be discerned in the key works of two poets, Sylvia Plath and Louise Glück. While offering readings of crucial poems, the thesis also examines the interrelations among trauma, memory and narrative as theorized by two contemporary psychiatrists, Bessel van der Kolk and Judith Herman. Both Plath and Glück wrote about personal and generational trauma after going through different experiences of abandonment. Absence, indirection and repetition provide the basis for literary techniques that allow their traumas to be better understood by authors and readers alike. The degree to which each poet succeeded in using poetry as a means for healing is discussed comparatively. The conclusion of the thesis emphasizes the possible role of writing in the recovery from trauma, but only when the writer receives the benefit of a support community that, in various ways, assists in recovery.